Heat hazard control in excavation engineering: Numerical simulation of heat transfer characteristics of high temperature tunnel with movable thermal insulation layer. (1st September 2022) - Li, Zijun; Wang, Junjian; Xu, Yu; Li, Gang; Yuan, Tianhui; Zhang, Mengsheng
Highlights: The use of movable thermal insulation layer (MTIL) in excavating tunnels was proposed. The thickening of the air layer causes the temperature to rise. The longer MTIL reduces the thermal insulation capacity. The moving grid is used to dynamically simulate the MTIL and heading face. Abstract: The current mine mining has entered the kilometres stage where the high geothermal has become a key factor limiting the tunnel excavation and operation. During the auxiliary ventilation of the mine, the heat exchange between the fresh air and the surrounding rock is serious and cannot meet the cooling demand. Therefore, thermal insulation must be adopted to control the heat transfer. However, the heat exchange between tunnel excavation area and operation area is different, so it is not economical to carry out full tunnel insulation. In order to optimize mine insulation technology and save construction cost, this paper proposes and verifies the feasibility of using movable thermal insulation layer (MTIL) for partial insulation of the excavation tunnel. The dynamic process of tunnel excavation and MTIL following is simulated by using a moving grid method. The results show that MTIL can effectively preserve the air cooling capacity and enhance the ventilation cooling effect. In addition, the thickness of the air layer is proportional to the convective heat flux of the surrounding rock. Whether to install the overall insulation layer and thermal conductivity have little effect on the insulation effect, but the best insulation layer length is 6–8 m. This study provides theoretical and technical support to improve the thermal environment of deep mine excavation work.